Brand Preference Sebagai Mediasi Faktor-Faktor Yang Mempengaruhi Purchase Intention - Rosalina Septiani; R.A Marlien (Journal of Economic, Bussines and Accounting (COSTING), 2023)
It is important for marketers how to make customers buy a product. The decline in the Avanza – Xenia market share in 2020 and 2021 indicates that purchase intention for the two products that carry out co-branding is decreasing. This study aims to examine the impact of brand equity and co-branding on purchase intention with brand preference as a mediator. The population in this study were potential consumers of Nasmoco Pemuda Semarang Dealers, with an estimated amount that could not be predicted, while the sample taken was 120 respondents. The sample collection method uses purposive sampling. The finding is brand equity, co-branding has a positive and significant effect on brand preference. Brand equity, co-branding and brand preference have a positive and significant effect on purchase intention so that brand preference is proven to act as a mediation. Keywords: Brand Equity, Co-branding, Brand preference, Purchase intention